AKUNTABILITAS PENGELOLAAN ALOKASI DANA KEPENGHULUAN DI KEPENGHULUAN PUJUD KECAMATAN PUJUD KABUPATEN ROKAN HILIR TAHUN ANGGARAN 2015 - Mizan, Husnul; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Pujud village District Pujud Regency of Rokan Hilir. The purpose of this research is to analyze the allocation of funds management accountability Pujud village fiscal year 2015. The method used in this research is descriptive qualitative method. To obtain the required data, the technique used in-depth interviews and documentation conducted by the researchers my self.The results showed that the management of the village allocation of funds in Pujud village from the planning process, the implementation process, and the process of accountability has yet to fully implement the principles of participation, of transparency, and accountability. This is because the government Pujud village not open access to information that can be seen communities. Headman of Pujud as mainly responsible for the management of the village allocation of funds also do not believe the people who have been designated as the implementation team. Then the government Pujud village from accountability tends only administratively. Direct accountability to the public through discussion forum evaluation is not implemented. This contrasts with the Regent of Rokan Hilir Regulation No. 8 of 2015 On Financial Management Kepenghuluan Rokan Hilir which requires the village allocation of funds management accountability in the overall responsibility directly to the public and BPK.Key Word: Accountability, Management, Village Funds Allocation